Protection of Muslim Consumers Against Food Products with Fake Halal Labels from The Perspective of Law Number 8 of 1999 Concerning Consumer Protection - Farihatun Azmi; Ernawati Ernawati (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2026)
The halal status of food products is considered a fundamental aspect for Muslim consumers because it is directly related to religious beliefs and the right to correct information. However, in practice, misuse of halal labels is still found, misleading consumers, one example being the case of the Widuran Fried Chicken Restaurant in Solo City. This study aims to examine the form of legal protection for Muslim consumers against the circulation of food products using fake halal labels, as well as to analyze the legal liability of business actors according to regulations on consumer protection and halal product guarantees. The research method applied is normative legal research conducted through a statutory regulatory approach and literature study, with qualitative data analysis. The results show that legal protection for Muslim consumers is implemented through two main instruments: a preventive mechanism that requires business actors to provide information regarding the halal status of products accurately, transparently, and responsibly, and a repressive mechanism in the form of administrative, civil, and criminal fines. Business actors proven to have included halal claims that are inconsistent with legal provisions can be held accountable for losses suffered by consumers. This study concludes that the implementation of related regulations is not yet fully optimal, so it is necessary to increase supervision and legal awareness of business actors to ensure the fulfillment of Muslim consumer rights.